Enhanced smoke wire technique in small scaled quasi-atmospheric boundary layer wind tunnel - Nurizzatul Atikha, Rahmat; Mujahid Husaimi, Che Hassan; Mohammad Rozaki, Ramli (2021)
For decades, wind tunnel is widely used for studying the response of aircrafts and, vehicles [Witkowski et al., 1989, Flanagan et al., 2007, and Cheli et al., 2010]. Nevertheless, wind tunnel is heavily employed over the last half century to examine the flow natures around various shapes of buildings and rigid bodies [Lin et al., 2005, Iqbal and Chan, 2016, Aristodemou et al., 2018, and Liu et al., 2019], to investigate wind pressure acting on building walls [Lou et al., 2012] which deeply related to the flow separation and vortex shedding [Rahmat et al., 2018], and to understand the strong wind effects on super tall buildings [Li et al., 2019] and high density residential area [Rahmat et al., 2016]